¿Bioética y derecho para qué y para quiénes? Discusiones en torno a la regulación de las técnicas de reproducción humana asistida en Colombia - Rincón Castellanos, Ximena (2012)
Bioethics and law for what and whom? Discussions about the Regulation of assisted reproductive techniques in Colombia The recent concern for the normative regulation of assisted reproduction techniques (ART), raises discussions about how to manage the embryos, how many times to use a sample, how to define parenthood, and other issues. However, it has not been questioned who would be favouredwith these regulations and what is their contribution to social equity and development for an entire country. Considering that the urgency to guarantee the sexual and reproductive rights —theoretical framework invoked to require ART— should be aimed at reaching a fair society.The proposed analysis will be undertaken considering the case of applying the ART for surrogate mothers in Colombia. The paper presents the context in which it is intended to apply the normative regulation, alongside the review of some conceptual and empirical contributions by Michael Sandel concerning trends in surrogate motherhood among «developed» and «third world» countries. This should allow considering the profiles of fertility in Colombia as a sign of inequality in our country.Subsequently, we will approach the current legal discussion in Colombia concerning surrogate motherhood, from the only case of surrogate motherhood resolved by the Colombian Constitutional Court and the bill projects presented in the Colombian Congress to regulate this issue. Finally,we will present some reflections and discussion on the normative regulation of the ART and surrogate gestation, and the law as a transmission belt of varied interests, that is, that it ought to lead to common good, solidarity and cooperation, and not simply function as a regulator that ensures the fulfilment of contracts.